2018
DOI: 10.1111/cbdd.13365
|View full text |Cite
|
Sign up to set email alerts
|

Blueprints for the rational design of therapeutic mutacin 1140 variants

Abstract: Lantibiotics represent a large untapped pipeline of attractive scaffolds for the development of novel antibiotics. Saturation mutagenesis was employed to substitute every amino acid of a lantibiotic called mutacin 1140 (MU1140), creating an unbiased expression library of 418 variants that was used to study the permissiveness to mutagenesis and the "drugability" of several compounds. Contrasting previous reports, the results from this study supported that not all residues involved in lanthionine bridge formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
(101 reference statements)
0
11
0
Order By: Relevance
“…The building block lanthionine 7 precursor was synthesized as previously reported, which was then followed by esterification to yield lanthionine OPfp ester 7 . Compound 7 was used as presented in Scheme .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The building block lanthionine 7 precursor was synthesized as previously reported, which was then followed by esterification to yield lanthionine OPfp ester 7 . Compound 7 was used as presented in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…Prior to the synthesis of bicyclic C/D ring, the AviCys was modified at position 22 to a cysteamine because it was previously shown that the AviCys functional group may not be essential for optimal antimicrobial activity ( Figure 1B). 43 This modification simplifies the synthetic The building block lanthionine 7 precursor was synthesized as previously reported, [10][11][12] which was then followed by esterification to yield lanthionine OPfp ester 7. Compound 7 was used as presented in Scheme 2.…”
Section: Synthesis Of Lanthionine Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…While mutacin 1140 (MU1140) is characterized by an excellent overall therapeutic profile (5,12,15), it suffers from limitations that impede its drugability and further clinical development. Building on the lessons learned from previous structure-function studies, key amino acid substitutions were pyramided into compounds that were further characterized in vitro and in vivo (16)(17)(18). Thirty-four years after the initial discovery of MU1140 by Hillman's group (19) and after the screening of over 700 compounds engineered with single and multiple (up to eight) amino acid substitutions in MU1140, two compounds with improved physicochemical, pharmacological, and therapeutic properties, OG716 and OG718, targeting Clostridium difficile in C. difficileassociated disease (CDAD) ( Fig.…”
mentioning
confidence: 99%